Próba okiełznania "ja" ? poglądy Józefa Czapskiego na przykładzie "Dzienników" = An attempt to control "I" ? an outlook of Józef Czapski's views on the margins of "Diaries" ["Dzienniki"] - Ludwicki, Konrad (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In my essay, I refer to "Wyrwane strony" ["Torn up Pages"] and touch upon Józef Czapski's problem of "struggling with oneself". This struggling is also the description of the writer's search of the Absolute and truth. Czapski in his search goes through a long and arduous intellectual journey. And above all, the artist appears to be the most authentic in the diary. There is no one dimension of existence and I try to signalize this matter following the Czapski's reflection.
Keywords: literatura; dziennik; sztuka; malarstwo; literature; diary; art; painting